Komi can't communicate Vol. 1 - Oda, Tomohito (San Francisco: VIZ, 2016)
Socially anxious high school student Shoko Komi would love to make friends, but her shyness is interpreted as reserve, and the other students keep her at a distance. Only timid Tadano realizes the truth, and despite his own desire to blend in, he decides to help her achieve her goal of making 100 friends
Keywords: Anxiety in adolescence -- Anxiety in adolescence Comic books, strips, etc. Juvenile fiction -- Bashfulness -- Bashfulness Comic books, strips, etc. Juvenile fiction